Effect of Potassium Application Rates on Sugarcane Yield in Soils with Different Non-Exchangeable Potassium Reserves and Fixation Capacity - Dimpho Elvis Elephant; Neil Miles; Pardon Muchaonyerwa (Agronomy, 2023)
Reliable fertilizer recommendations should account for factors influencing nutrient supply, including non-exchangeable potassium (K) reserves and fixation capacity, to ensure optimum crop yields. The combined effects of non-exchangeable K reserves and fixation capacity of soils on crop response to K application has not been evaluated. This study evaluated the response of sugarcane yields to K application on two soils with contrasting combinations of non-exchangeable K reserves and fixation capacity. Potassium was applied at 0, 120, and 240 kg K ha−1 at the commencement of the field trials and after each harvest on an umbric Acrisol, which had low non-exchangeable K reserves and medium K fixation capacity, and a cutanic Acrisol, which had ‘very high’ non-exchangeable K reserves and fixation capacity. Sugarcane stalk and sucrose yield, leaf, and exchangeable K were measured for each season. In the umbric Acrisol, a lower sucrose yield was measured in the 240 kg K ha−1 treatment compared to the control for the plant crop, but this application rate had higher yields for the second ratoon. In contrast, there was no yield response to K application in cutanic Acrisol. This study indicated the importance of non-exchangeable K reserves and fixation capacity when calculating K requirements and conducting field calibration studies.